FRI0362 Mineralized, Pegylated Hyaluronic Acid Nanoparticles for Ph-Responsive Delivery of Methotrexate in Inflammatory Arthritis. (10th June 2014) - Sung, S.; Alam, M.M.; Han, H.S.; Kang, J.H.; Hasan, F.A.; Jung, M.J.; Park, J.H.; Kang, Y.M.
Abstract : Background: Targeted delivery to inflamed joint and site specific drug release are the key factors for effective therapy against inflammatory arthritis. The critical dose-limiting factor for methotrexate, an anchor drug for inflammatory arthritis, is toxicity on the liver and bone marrow, which may overcome by targeted delivery based on the microenvironment. Objectives: The aim of this study is to investigate intracellular delivery and in vivo efficacy of modified hyaluronic acid nanoparticles (HANPs) as a carrier for methotrexate. Methods: As a potential carrier of methotrexate (MTX), HANP were synthesized by self-assembly from hydrophobic HA derivatives and chemically modified including PEGylation and mineralization to enhance target selectivity in inflammatory arthritis. Cellular uptake was evaluated using human monocytes/macrophages and sinusoidal endothelial cells (HSEC) and murine macrophages derived from CD44- and stabilin-2-deficient mice. Biodistribution and therapeutic efficacy were evaluated in collagen-induced arthritis (CIA) mice. Results: In release kinetic studies, a sustained release pattern of MTX was observed for MTX-loaded bare HANPs, which was not dependent on the pH. Release of MTX from mineralized PEGylated HANP (mpHANP), however, was much higher in acidic condition compared with HANP and PEGylated HANP (pHANP). Both differentiated macrophages and HSEC effectively endocytosed HANP-Cy5.5, which was inhibited by wortmannin and chlorpromazine, but not by dynasore, amiloride, nystatin, or LY294002. Rifampin, an inhibitor of organic acid transporter, inhibited suppressed the cellular uptake of HANP in cooperation with wortmannin. Intracellular accumulation of HANP was not reduced in murine macrophages from CD44- and stabilin-2-deficient mice. Subcellular trafficking of HNAP was studied using Rab5, lysotracker, endoplasmic reticulum tracker, and mitotracker. HANP-Cy5.5 colocalized with early endosomes which later colocalized with lysosomes, implicating that MTX enclosed in HANP may be released at late endosomes in macrophages. Systemic administration of HANP-Cy5.5 revealed accumulation on inflamed joints as well as liver on the real-time optical imaging. Ratios of fluorescence intensities over paw and liver in CIA mice were significantly improved with mpHANP compared to HANP and pHANP. Histologic evaluation confirmed the enhanced selectivity for joint accumulation of mpHANP-Cy5.5. Treatment of CIA mice with high dose of MTX (50 mg/kg) resulted in serious toxicity as well as therapeutic efficacy. In contrast, repeated treatment with MTX in mpHANP (50mg/kg of MTX) did not have toxicity on body weight measurement and biochemical and hematological evaluation, but with remarkable efficacy in ameliorating arthritis. Conclusions: The present study showed that mpHANP nanocarrier for MTX, which release MTX in a pH-responsive manner after receptor-mediated endocytosis, remarkably enhanced target selectivity to inflamed joint tissues and thus may serve as a promising carrier for MTX in inflammatory arthritis. Acknowledgements: This study was supported by a grant from the Korea Health Technology R&D Project, Ministry of Health & Welfare, Republic of Korea (A101706). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3589